The Influence of Audio Visual Learning Media Based on Life Skills Regarding Student Learning Outcomes - Nomleni, Fransina Thersiana; Manek, Silvester; D. Koroh, Tince (Jurusan Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Timor, 2024)
Learning requires interesting learning media that can support the theory taught by the teacher. This study aims to determine: the effect of using audio-visual media based on life skills on the learning outcomes of students of SMA Negeri 3 Fatuleu. The research method used experimental method with quantitative approach. The research design was pre-testposttest control group design. The study population was Class X IPA students of SMA Negeri 3 Fatuleu, totalling 26 people. The sampling technique was saturated sample technique. The instrument used was a test instrument in the form of a pretest and posttest. The data has been analysed using descriptive analysis with the help of SPSS. Based on the data analysis of the achievement of pretest learning outcomes with a percentage of 38% in the low category and posttest learning outcomes with a percentage of 72% in the very high category, it can be said that there is a very significant effect in the use of media, the t test shows that there is a significant effect on the use of life skill-based audio visual learning media in the learning process. Based on these facts, it shows that the influence of life skill-based audio visual media has a very good influence and can increase the level of understanding of students in understanding the concepts taught. The increase in learning outcomes is because by using existing media students are required to think actively, creatively and students must also draw conclusions from the material taught so that student interest in learning increases resulting in improved learning outcomes.